Catalyst choice impacts aromatic monomer yields and selectivity in hydrogen-free reductive catalytic fractionation. Issue 12 (1st September 2022) - Kenny, Jacob K.; Brandner, David G.; Neefe, Sasha R.; Michener, William E.; Román-Leshkov, Yuriy; Beckham, Gregg T.; Medlin, J. Will
Abstract : Pd/C and Pt/C show high activity for hydrogen-free reductive catalytic fractionation compared to Ru/C and Ni/C. Abstract : Hydrogen-free reductive catalytic fractionation (RCF) is a promising method to extract and depolymerize lignin from native biomass without the use of external hydrogen gas. Here, we show that Pt/C and Pd/C achieve comparable monomer yields regardless of hydrogen pressure, whereas Ru/C and Ni/C show lower yields under H2 -free conditions. Ru/C and Ni/C primarily perform hydrodeoxygenation regardless of the hydrogen pressure, but Pt/C and Pd/C demonstrated the ability to form both ethyl products from dehydrogenation and propanol products through hydrogenation depending on the presence of external H2 . Adding water to the solvent increased HDO selectivity to propyl products for both Pt/C and Pd/C. Monomer yields from poplar RCF showed similar trends in yield and selectivity to reactions with the model compound coniferyl alcohol, suggesting that H2 -free RCF performance is dictated by the stabilization rate of reactive monomer intermediates.